Hybrid type-2 wavelet-neuro-fuzzy network for prediction of business processes - Bodyanskiy, Yevgeniy; Vynokurova, Olena (Sieć typu hybrid type-2 wavelet-neuro-fuzzy network do prognozowania procesów biznesowych, 2011)
In the paper the hybrid type-2 wavelet-neuro-fuzzy-system architecture is proposed. Such a system is approximated by an ensemble of type-1 wavelet-neuro-fuzzy-systems. The distinctive feature of the proposed system is usage of the type-2 fuzzy wavelets membership functions in the antecedent layer and the adaptive multidimensional wavelets as the activation functions in the consequent layers. The learning algorithms for all antecedent and consequent functions’ parameters and procedure of model type-reduction and defuzzification are proposed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 9-21
Keywords: fuzzy systems; network systems; learning algorithm